RANCANG BANGUN MODEL STRATEGI SISTEM PENUNJANG KEPUTUSAN PENGEMBANGAN AGROINDUSTRI BERBASIS KAKAO MELALUI POLA JEJARING USAHA - Husain Syam, M.Syamsul Ma’arif, Eriyatno, Illah Sailah, Machfud dan M.Said Didu (Jurnal Teknologi Industri Pertanian, 2006)
ABSTRACTA research on design model of cocoa-based agro-industry through small and medium scale business network pattern has been conducted with system approach which aim was to establish its decision supporting system. The research finding indicated that the application of system was able to synthesize ideas of inter-disciplines; therefore it would improve the effectiveness of decision-making quality integratively. The research produced decision-supporting system model of comprehensive cocoa-based agro-industry through small and medium scale business network pattern which harmoniously accommodate the needs of stakeholders and should be effectively used by the decision makers facing dynamic change and information development. The decision supporting system may also be useful for planning management and implementation of synergizing strategy of various stakeholders in specific region. This model also includes the evaluation of the best-processed cocoa and the use of the appropriate technology.  In addition, this model would arrange  institutional development of agro-cocoa system and found key elements such as needs, constraints, aims, social sectors concerned, social institutions involved, and parameters. Finally this model can analyze the feasibility of agro-cocoa business which is generically designed from the plantation and post-harvest to processing industry as an integrated business.  Keywords :    Design strategy of Dicision support system, cocoa-based agroindustry, Business network pattern   models